Finite element analysis of residual stress in 2.25Cr-1Mo steel pipe during welding and heat treatment process. (November 2019) - Ren, Sendong; Li, Suo; Wang, Yifeng; Deng, Dean; Ma, Ninshu
Abstract: The circumferential butt-welded pipe was fabricated using 2.25Cr-1Mo steel and then subjected to local post-weld heat treatment (LPWHT) for releasing residual stress after multi-pass welding. The sectioning method was employed to measure residual stress. Based on SYSWELD software, a thermo-metallurgical-mechanical coupled computational approach was developed to analyses the residual stress distribution on 2.25Cr-1Mo welded pipe. A three-dimensional finite element model and moving heat source model were employed in simulation. The effects of solid-state phase transformation (SSPT), tempering as well as creep were considered simultaneously. The effectivity of computational approach was verified by experimental measurement. The simulation results showed that SSPT could induce an undulating stress profile and large stress gradient in welded zone. The stress gradient could be reduced during LPWHT while there were stress peaks at the edges of heated region. Tempering effect could decrease the residual stress at high-stress region by material softening and yielding. Creep caused a global transformation from elastic strain to plastic strain, which led to a macro-scale stress relaxation. It is necessary to consider SSTP, tempering as well as creep in material model for more accurate simulation results.